Overexpression of miR-142-5p and miR-155 in gastric mucosa-associated lymphoid tissue (MALT) lymphoma resistant to Helicobacter pylori eradication. - Yoshimasa Saito (Public Library of Science (PLoS), 2012)
microRNAs (miRNAs) are small non-coding RNAs that can function as endogenous silencers of target genes and play critical roles in human malignancies. To investigate the molecular pathogenesis of gastric mucosa-associated lymphoid tissue (MALT) lymphoma, the miRNA expression profile was analyzed. miRNA microarray analysis with tissue specimens from gastric MALT lymphomas and surrounding non-tumor mucosae revealed that a hematopoietic-specific miRNA miR-142 and an oncogenic miRNA miR-155 were overexpressed in MALT lymphoma lesions. The expression levels of miR-142-5p and miR-155 were significantly increased in MALT lymphomas which do not respond to Helicobacter pylori (H. pylori) eradication. The expression levels of miR-142-5p and miR-155 were associated with the clinical courses of gastric MALT lymphoma cases. Overexpression of miR-142-5p and miR-155 was also observed in Helicobacter heilmannii-infected C57BL/6 mice, an animal model of gastric MALT lymphoma. In addition, miR-142-5p and miR-155 suppress the proapoptotic gene TP53INP1 as their target. The results of this study indicate that overexpression of miR-142-5p and miR-155 plays a critical role in the pathogenesis of gastric MALT lymphoma. These miRNAs might have potential application as therapeutic targets and novel biomarkers for gastric MALT lymphoma.